2012
DOI: 10.5511/plantbiotechnology.12.0127a
|View full text |Cite
|
Sign up to set email alerts
|

The effects of introduction of a fungal glutamate dehydrogenase gene (<i>gdhA</i>) on the photosynthetic rates, biomass, carbon and nitrogen contents in transgenic potato

Abstract: Glutamate dehydrogenase (GDH) catalyzes the reversible amination of 2-oxoglutarate with ammonium to form glutamate. GDH functions in nitrogen assimilation in microorganisms, such as Aspergillus nidulans. However, in plants, glutamine synthetase, not GDH, carries out nitrogen assimilation. Here, we report the e ects of introduction of the gdhA gene, encoding NADP(H)-dependent glutamate dehydrogenase, from A. nidulans into potato. We analyzed the resulting changes of photosynthesis, biomass, carbon and nitrogen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…Our results are consistent with those of several previous studies that showed high NADP(H)-GDH activities in transgenic rice or potato by the introduction of a gdh gene from fungi or bacteria (Abiko et al, 2010;Du et al, 2014;Egami et al, 2012;Zhou et al, 2014). Introduction of an exogenous GDH gene into tobacco (Mungur et al, 2005) or crop plants may improve NH + 4 assimilation, raise biomass production, and enhance the absorption and utilization of nitrogen.…”
Section: Effect Of Gdha Expression On Nitrogen Content and Concentratsupporting
confidence: 95%
See 1 more Smart Citation
“…Our results are consistent with those of several previous studies that showed high NADP(H)-GDH activities in transgenic rice or potato by the introduction of a gdh gene from fungi or bacteria (Abiko et al, 2010;Du et al, 2014;Egami et al, 2012;Zhou et al, 2014). Introduction of an exogenous GDH gene into tobacco (Mungur et al, 2005) or crop plants may improve NH + 4 assimilation, raise biomass production, and enhance the absorption and utilization of nitrogen.…”
Section: Effect Of Gdha Expression On Nitrogen Content and Concentratsupporting
confidence: 95%
“…Overall, the transgenic lines with higher tolerance to salt stress maintained higher NADP(H)-GDH activity, which played an important role in decreasing the NH + 4 accumulation in tissues under salt stress. Egami et al (2012) introduced a fungal gdhA, encoding NADP(H)-GDH, from A. nidulans into potato and found that transgenic plants had enhanced photosynthetic rates, biomass production, and carbon and nitrogen contents compared with non-transgenic plants. In our study, leaf areas were markedly larger for the high gdhA-expressors than control line at the seedling stage (Figure 4).…”
Section: Effect Of Gdha Expression On Nitrogen Content and Concentratmentioning
confidence: 99%
“…Positive results were achieved for genes of a nitrate reductase ( OsNR2 , Gao et al, 2019b ), glutamine synthetases ( NtGS1 , Oliveira et al, 2002 ; ZmGln1-3 , Martin et al, 2006 ; SbGS1 , Urriola and Rathore, 2015 ; bacterial GS I , Zhu et al, 2015 ; DvGS2 , Zhu et al, 2014 ), glutamate synthases ( MsNADH-GOGAT , Chichkova et al, 2001 ; OsGOGAT1 , Lee et al, 2020a ), asparagine synthetases ( OsASN1 , Lee et al, 2020b ; E. coli EcasnA , Seiffert et al, 2004 ), nitrate ( OsNRT1.1A , Wang et al, 2018b ; ( At ) NC4N , a synthetic gene construct based on Arabidopsis gene sequences, Chen et al, 2020 ), and amino acid transporters ( PsAAP1 , Perchlik and Tegeder, 2017 ) as well as for glutamate dehydrogenases ( Trichurus sp. TrGDH , Du et al, 2019 ; C. ehrenbergii CeGDH , Zhou et al, 2015b ; P. cystidiosus PcGDH , Zhou et al, 2014 ; E. cheralieri EcGDH , Tang et al, 2018 ; E. coli EcgdhA , Ameziane et al, 2000 ; Lightfoot et al, 2007 ; Aspergillus nidulans AngdhA , Egami et al, 2012 ) and autophagy-related proteins ( AtATG8 , Chen et al, 2019 ; OsATG8a , Yu et al, 2019 ; OsATG8b , Zhen et al, 2019a , Fan et al, 2020 ; OsATG8c , Zhen et al, 2019b ). Pathways of N (re)assimilation, AA synthesis and conversion (AA (1) to AA (2) ), organelle and N metabolite degradation, as well as N phloem loading and xylem-phloem exchange (arrows with circle) are shown.…”
Section: Role Of Inorganic Nitrogen Uptake and Partitioning In Nuementioning
confidence: 99%
“…Specifically, expression of EcgdhA from E. coli in tobacco and maize resulted in increased biomass under sufficient N conditions (Ameziane et al, 2000 ) and increased seed yield under high N supply (Lightfoot et al, 2007 ), respectively. Further, expression of AngdhA from Aspergillus nidulans in potato ( Solanum tuberosum ) caused increased photosynthesis rates, tuber numbers and tuber dry weight, as well as improved NUE at moderate and low N levels (Egami et al, 2012 ). In rice, increases in NUE and/or grain yield were achieved at low N when fungal GDH from Cylindrocarpon ehrenbergii ( CeGDH ) or Eurotium cheralieri ( EcGDH ) were expressed (Zhou et al, 2015b ; Tang et al, 2018 ).…”
Section: Contribution Of Source Leaf Nitrogen Metabolism and Amino Acmentioning
confidence: 99%
“…A number of studies have demonstrated the advantages of transgenic versus control plants under N deficiency conditions. A transfer of a gdhA gene from Aspergillus nidulans to potato led to an increase in both total dry biomass and tuber biomass in the greenhouse [ 109 ]. Interestingly, with normal N availability, only one line had an increase in biomass, whereas at lower N levels, four other lines did.…”
Section: Genetic Engineering Of Nitrogen Metabolismmentioning
confidence: 99%